An analysis of health facility preparedness for major incidents in Kampala - Kalanzi, Joseph (Division of Emergency Medicine, 2016)
Background & Objectives: Major incidents occur commonly in Uganda, but little is known about either local hazards which risk causing major incidents, or health system preparedness for such events. Understanding risk and current preparedness is the first step in improving response. Methods: We undertook a cross - sectional study across four teaching hospitals in Kampala (Mulago National Referral Hospital, Nsambya Hospital, Mengo Hospital and Lubaga Hospital). A local geographic area Hazard Vulnerability Analysis (HVA) f or each site was combined with a key informant questionnaire and standardized facility checklist within the hospitals. Data collected included status of major incident committees, operational major incident plans and facility major incident operation centres, bed capacity, equipment and supplies and staffing. The HVA assessed the human impact, impact on property and on business of the hazards as well as measures for mitigation (preparedness, internal response and external response) in place at the hospitals. Results: Only one of the four hospitals was found to have had an operational major incident plan. The designated coordinator for major incidents across all facilities was mostly a general surgeon; no funds were specifically allocated for planning .All hospitals have procedures for triage, resuscitation, stabilization and treatment. None of the facilities had officially designated a major incident committee. All the facilities had sufficient supplies for daily use but none had specifically stock piled any reserves for major incidents. All hospitals were staffed by at least a medical officer, clinical officers, nurses and a specialist with procedures for mobilizing extra staff s for major incidents. Some staffs had received some emergency care training in courses namely basic life support, advanced trauma life support, primary trauma care and emergency triage and treatment but no team had received training in major incident response. Only one hospital carried out annual simulation exercises. Incidents involving human hazards specifically bomb threats, road crash mass casualty incidents, civil disorder and epidemics posed the highest risk to all four hospitals and yet preparation and response measures were inadequate. Conclusion: Hospitals in Kampala face a wide range of hazards and frequent major incidents but despite this they remain under - prepared to respond. Large gaps were identified in as far as staffing, equipment and infrastructure.